Frangible Glider Development. - Vanderklein, Ian A. (Tufts Archival Research Center, 2014)
Abstract: There is a demonstrated need for an aerial reconnaissance glider that can disappear without a trace. To fill this need, a frangible glider was developed with a rigid airframe made up of many component pieces held together in compression by a tension member. The airframe can be triggered to fall apart into its component pieces by severing the tension member. The primary failure modes of the glider were identified and a mathematical model of the wing was developed to better analyze these failure modes. The model indicated that tipping failure due to an applied moment on the wing causing separation between the wing and the body of the glider was the most likely cause of failure. Experiments were performed to test whether the model accurately portrayed failure of the wing, and to test the flight characteristics of the glider prototype. It was found that the experimental and mathematical data had similar curves although they differed at what moment caused initial tipping by about 1 lb*in. The flight test showed that many components of the glider can fail to perform correctly and better integration of glider components was necessary. However, it was demonstrated that the frangible airframe concept is a viable product.